Contemporary furniture : an international review of modem furniture, 1950 to the present - Jurgen; Sembach, Klaus (: The Design Council, 1982)
Contiene: classical models reproduced, klassische modelle in neuproduktion, chairs and armchairs, stuhle und sessel, seating arrangements, sotas, and beds, sitzgruppen, sofas und betten,office furmiture buromodel, cabinets and shelves, kastenmodel und regale, nursery and school furniture, kinder und schulmobel
Keywords: ARTES VISUALES